1994
DOI: 10.1007/bf01694759
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risks among female farmers in Sweden

Abstract: There are few studies on cancer risks among female farmers, particularly on breast cancer and cancer in female genital organs. We have conducted a cohort study of cancer risk among 50,682 women with occupations in agriculture according to the Swedish 1970 census. The cohort was followed up in the nationwide, population-based, Cancer-Environment Register from 1 January 1971 until death or until 31 December 1987. Expected number of cases was based on annual cancer incidence in five-year age groups. The standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 54 publications
9
39
2
Order By: Relevance
“…Four studies were restricted to female farmers (57)(58)(59)(60), and 7 studies reported results for both male and female farmers (6,39,40,(61)(62)(63)(64). Four studies (20,53,65,66) lacked information about gender.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were restricted to female farmers (57)(58)(59)(60), and 7 studies reported results for both male and female farmers (6,39,40,(61)(62)(63)(64). Four studies (20,53,65,66) lacked information about gender.…”
Section: Resultsmentioning
confidence: 99%
“…One study (12) was restricted to women, and 4 studies provided data for female farmers (table 2). Nine studies provided data on malignant melanoma and nonmelanotic skin cancer (table 3).…”
Section: Maferial and Methodsmentioning
confidence: 99%
“…64,65 Studies in the United States, Canada and Europe have reported 6-28% reductions in overall mortality and/or cancer mortality when compared to rates in the general population. 64,[66][67][68][69][70][71][72][73][74][75] The lower overall mortality rate among farmers may be attributable to healthier lifestyle practices. As an occupational group, farmers have a lower incidence of smoking-related cancers, 64,66,67,70,72,73 reflecting lower smoking rates.…”
Section: Agriculture and Farmingmentioning
confidence: 99%
“…[76][77][78][79] In addition, agricultural work may be considered a salubrious lifestyle, encompassing physically demanding activities that require exercise, strength and stamina, as well as dietary choices rich in fresh foods. 76 Findings from studies of farming and multiple myeloma have been mixed, however, ranging from relative risk estimates below 1.0 64,65,67,[69][70][71][72][73] to increased risks in excess of 3-fold, 70,71 either overall or for specific subgroups.…”
Section: Agriculture and Farmingmentioning
confidence: 99%